A High Power, High Step-up DC/DC Converter for Fuel Cell Range Extender Vehicles - Liu, Hanbo (My University, 2025)
Industry and researchers are investigating both battery electric vehicles and fuel cell hybrid vehicles to aid in the transition to a sustainable transportation system due to many advantages brought by both vehicles. However, considering the challenges for battery electric vehicles, such as range anxiety, high cost due to large batteries, and long charging times, and the inconvenience of using fuel cell hybrid vehicles due to the impossibility of charging at home, fuel cell range-extender vehicles (FCREVs) have been proposed since they exhibit some advantages over each, and have become a recent focus. In detail, FCREVs combine the advantages of both technologies with a plug-in battery and smaller fuel cell to allow convenient overnight charging and high-efficiency operation for the regular commute, and to allow longer driving ranges and quick refueling for long-distance driving days, when the fuel cell is used. Since the fuel cell is a costly component, FCREV designs with smaller fuel cells are attractive from a cost-reduction standpoint. However, small fuel cells also generally have low output voltages, which means a higher voltage gain is required across the fuel cell DC/DC converter to transfer power to the high-voltage battery or dc-link. This presents a power electronic challenge, as few DC/DC converter designs focus on both high-gain and high-power applications. Thus, this thesis first reviews and investigates published converter topologies that are potentially suitable for achieving high-gain and high-power at the same time. Then, this thesis proposes a new DC/DC converter topology for high-gain, high-power applications such as the FCREV. The proposed topology is an interleaved boost structure with a voltage doubler and one voltage multiplier stage. Operating principles and equations of the main 7 components design are all introduced, followed by detailed simulation results from PLECS to compare a 20-kW design with the other most relevant topologies from the literature. The simulation results show that the proposed converter achieves the highest efficiency across the considered operating range. The structure of the proposed converter also assures that both input current ripple and output voltage ripple are performing well for the health and lifespan of the fuel cell and high voltage battery of the vehicle. A 3-kW prototype is also built and tested to verify the performance of the proposed topology, and the experimental results show an efficiency of 95.28% at 3 kW with a gain of 9 and an efficiency of 93.09% at 2 kW with a gain of 13.2.
Keywords: DC-DC power converters, efficiency, fuel cells